Konflik Agama Dalam Media Berita Online (Kajian Kritis Pemberitaan Konflik Cikeusik Dalam Portal VIVA.CO.ID Pada Periode Bulan Februari - M. Fikri AR. (KOM & REALITAS SOSIAL, 2012)
This study aims to determine how the construction of news Ahmadiyya conflict in Cikeusik at VIVA.co.id as online news media, at the period February 2011. The main problem is studied and researched based on data 170 Cikeusik conflict news, flt out with in depth interviews with media managers, therefore resulting the conclusions and specific findings. The method that used in this study is Critical Discourse Analysis (CDA) from Norman Fairclough, which generally includes a multilevel analysis, from the micro level (text), meso level (discourse practice), and the macro level (sociocultural) which is jointly implemented to read, analyze and interpret the texts of Cikeusik conflict news. In this case, researcher found that the tendency of each party that contribute in Cikeusik conflict have influence and different roles. The results of the study found a trend that the mass of the attacker is constructed as a brutal aggressor; on the other hand, the conflict victims constructed as a faction with psychological trauma. The model construction awakened conflict in it is a spiral of conflict, while construction therein ideology is the ideology of liberal that fill of expression, free-moving, by making the conflict incidents as the main element of reporting.